Angle-dependent strong-field ionization and fragmentation of carbon dioxide measured using rotational wave packets - Lam, Huynh Van Sa; Yarlagadda, Suresh; Venkatachalam, Anbu; Wangjam, Tomthin Nganba; Kushawaha, Rajesh K.; Cheng, Chuan; Svihra, Peter; Nomerotski, Andrei; Weinacht, Thomas; Rolles, Daniel; Kumarappan, Vinod (My University, 2020)
In this work, we experimentally study the angle-dependent single ionization of carbon dioxide (CO2) by linearly and circularly polarized pulses. The angle dependence of the ionization probability by linearly polarized pulses extracted from time-domain measurements on an impulsively excited rotational wave packet is compared with data obtained from a direct angle-scan measurement. The results from the measurement with linear and circular polarization are consistent with the adiabatic ionization approximation. We extend the time-domain method to extract the dependence of the asymptotic momentum distribution of fragment ions on the orientation of the molecular axis, and apply it to investigate dissociative double ionization of CO2. We show that such measurements can directly test the validity of the axial recoil approximation.